Temporal Evolution of Target Representation, Movement Direction Planning, and Reach Execution in Occipital–Parietal–Frontal Cortex: An fMRI Study. (15th October 2016) - Cappadocia, David C; Monaco, Simona; Chen, Ying; Blohm, Gunnar; Crawford, J Douglas
Abstract: The cortical mechanisms for reach have been studied extensively, but directionally selective mechanisms for visuospatial target memory, movement planning, and movement execution have not been clearly differentiated in the human. We used an event-related fMRI design with a visuospatial memory delay, followed by a pro-/anti-reach instruction, a planning delay, and finally a "go" instruction for movement. This sequence yielded temporally separable preparatory responses that expanded from modest parieto-frontal activation for visual target memory to broad occipital–parietal–frontal activation during planning and execution. Using the pro/anti instruction to differentiate visual and motor directional selectivity during planning, we found that one occipital area showed contralateral "visual" selectivity, whereas a broad constellation of left hemisphere occipital, parietal, and frontal areas showed contralateral "movement" selectivity. Temporal analysis of these areas through the entire memory-planning sequence revealed early visual selectivity in most areas, followed by movement selectivity in most areas, with all areas showing a stereotypical visuo-movement transition. Cross-correlation of these spatial parameters through time revealed separate spatiotemporally correlated modules for visual input, motor output, and visuo-movement transformations that spanned occipital, parietal, and frontal cortex. These results demonstrate a highly distributed occipital–parietal–frontal reach network involved in the transformation of retrospective sensory information into prospective movement plans.